2005
DOI: 10.1111/j.1469-1795.2005.00006.x
|View full text |Cite
|
Sign up to set email alerts
|

Gamebird vulnerability to forest fragmentation: patch occupancy of the crested guineafowl (Guttera edouardi) in Afromontane forests

Abstract: The forest-restricted and social crested guineafowl Guttera edouardi is believed to be declining in Afromontane forests due to the fragmentation of its habitat. Incidence functions, derived from presence/absence data from 82 forests, were used to investigate area, isolation and environmental/anthropogenic effects on guineafowl patch occupancy and persistence. The incident probability of the guineafowl increased significantly with increasing area, but was invariant with increasing isolation distance from a puta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 35 publications
(48 reference statements)
1
9
0
Order By: Relevance
“…The result that patch size is the best single predictor for capercaillie occurrence is paralleled by other studies of forest‐dwelling species (Blake and Karr 1984, Rolstad 1991, Lawes et al 2006). Being a forest‐interior species, capercaillie appears to be very sensitive to area effects.…”
Section: Discussionsupporting
confidence: 66%
“…The result that patch size is the best single predictor for capercaillie occurrence is paralleled by other studies of forest‐dwelling species (Blake and Karr 1984, Rolstad 1991, Lawes et al 2006). Being a forest‐interior species, capercaillie appears to be very sensitive to area effects.…”
Section: Discussionsupporting
confidence: 66%
“…For example, a comparison of species numbers in nine small forest fragments with that in a larger forest site in the east Usambara mountains, Tanzania, showed that understorey species were absent from the former (Newmark 1991). Forest sensitive species such as the Crested Guineafowl Guttera edouardi are more likely to occur in larger fragments although isolation may be relatively unimportant (Lawes et al . 2006).…”
Section: Discussionmentioning
confidence: 99%
“…For example, a com-parison of species numbers in nine small forest fragments with that in a larger forest site in the east Usambara mountains, Tanzania, showed that understorey species were absent from the former (Newmark 1991). Forest sensitive species such as the Crested Guineafowl Guttera edouardi are more likely to occur in larger fragments although isolation may be relatively unimportant (Lawes et al 2006). A comparison of the avifauna communities in mature forest and adjacent disturbed forest in the Tanzania-Malawi mountains showed that there were more species in disturbed than undisturbed forest owing to the presence of edge species in the former (Fjeldsa 1999).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The fitted detection function reflects both the decrease in detectability with distance and the lower proportion of animals that are potentially detectable (Buckland et al 2001). For each sighting, we recorded the number of birds and habitat type (according to Kikula 1980;Caro 1999), but because of small sample size we pooled habitat types into two categories, closed habitat (woodlands and bushlands) and open habitat (grasslands, wooded grasslands, bushed grasslands and cultivated lands).…”
Section: Questionnaire Datamentioning
confidence: 99%